DISTANCE LEARNING IN THE PANDEMI COVID-19 SITUATION: EFL LEARNING UNDER INDONESIA'S HEALTH PROTOCOL - Mohamad Syafri; Saude Saude (IJEE (Indonesian Journal of English Education), 2022)
ABSTRACTThe implementation of the Distance Learning policy in all schools in Indonesia due to the Covid-19 outbreak has affected the teaching process. This quantitative research elucidates how EFL teaching and learning cope with the procedure. Two aspects will be illuminated in this research; the first is how schools and teachers prepare for online-based distance learning. The second is how the learning process conducts during the distance learning policy. This research collected data from 167 participants, including vice principals, EFL teachers, IT operators, and students from senior high schools in Palu, Central Sulawesi Provinces. The data was analyzed following the Illuminative Evaluation model by Parlett and Hamilton. The results found that schools and teachers are more well-equipped and prepared than the students. However, some students still face difficulties due to the absence of facilities and geographical situation. In the learning process, more flexible policies in class are still implemented by teachers, especially for students with limited access and lack of affective aspects. ABSTRAKPenerapan kebijakan Pembelajaran Jarak Jauh ke seluruh sekolah di Indonesia akibat wabah Covid-19 berdampak pada proses belajar mengajar. Penelitian kuantitatif ini menjelaskan bagaimana pengajaran dan pembelajaran Bahasa Inggris harus beradaptasi dengan protocol kesehatan. Dua aspek yang disoroti dalam penelitian ini; pertama, bagaimana sekolah dan guru mempersiapkan pembelajaran jarak jauh berbasis online. Kedua, bagaimana proses pembelajaran dilakukan selama penerapan pembelajaran jarak jauh. Penelitian ini mengumpulkan data dari 167 peserta, termasuk wakil kepala sekolah, guru Bahasa Inggris, operator IT, dan siswa dari sekolah menengah atas di Palu, Provinsi Sulawesi Tengah. Data dianalisis dengan model Illuminative Evaluation oleh Parlett dan Hamilton. Hasilnya ditemukan bahwa sekolah dan guru lebih siap dibandingkan dengan siswa. Beberapa siswa masih menghadapi kesulitan karena tidak adanya fasilitas dan situasi geografis. Dalam proses pembelajaran, guru masih harus memberikan kebijakan yang lebih fleksibel di kelas, terutama bagi siswa dengan akses yang terbatas dan aspek afektif yang kurang.